Probing the potential of bioactive compounds of millets as an inhibitor for lifestyle diseases: molecular docking and simulation-based approach - Nagre, Kajal; Singh, Nirupma; Ghoshal, Chandrika; Tandon, Gitanjali; Iquebal, Mir Asif; Nain, Tarsem; Bana, Ram Swaroop; Meena, Anita (Frontiers in Nutrition, 2023)
Millets are becoming more popular as a healthy substitute for people with lifestyle conditions like diabetes, cardiovascular disease, intestinal issues, or gluten sensitivities. They offer dietary fiber, polyphenols, fatty acids, minerals, vitamins, protein, and antioxidants. Millet-based foods are regarded as potential prebiotics because they can boost the probiotics' viability or functionality, which had a beneficial effect on health. We all are aware of the numerous health advantages of bioactive molecules or secondary metabolites of plants, but their mode of operation and functions are not well-defined. The nutritional importance of millets leads to the present in-silico study of selective bioactive compounds docked against the targets of lifestyle disease viz., diabetes, hypertension, and atherosclerosis using This is a provisional file, not the final typeset article molecular docking and molecular simulations approach. The docking results revealed that bioactive compound flavan-4-ol ,among all the fifty compounds studied, best docked to all the four targets of lifestyle diseases viz., Human Dipeptidyl Peptidase IV (-5.94 kcal mol -1 binding energy), Sodium-Glucose Cotransporter-2 (-6.49 kcal mol -1 ) diabetes-related enzyme, the Human Angiotensinconverting enzyme (-6.31 kcal mol -1 ) which plays a significant role in hypertension, and Proprotein convertase subtilisin Kexin type 9 (-4.67 kcal mol -1 ) for atherosclerosis. Molecular dynamics simulation analysis substantiates that the flavan-4-ol forms better stability complex with all the targets.ADMET profiles further strengthened the candidature of flavan-4-ol bioactive compound to be considered for trial as an inhibitor of targets DPPIV, SGLT2, PCSK9, hACE. It is suggested to conduct more research to take Flavon-4-ol into account when producing new medicines from millets for these lifestyle diseases.